2012
DOI: 10.1589/jpts.24.863
|View full text |Cite
|
Sign up to set email alerts
|

Differences of Isometric Internal and External Hip Rotation Torques among Three Different Hip Flexion Positions

Abstract: Abstract.[Purpose] The aim of this study was to investigate isometric internal and external rotation torques of the hip at three different flexed positions of the hip.[Subjects] Twenty healthy university students.[Methods] Isometric internal and external maximum rotation torques of the hip on both sides were measured using a torque machine in the recumbent, semi-recumbent and sitting positions. Dependent variables were the isometric internal and external rotation peak torques of the hip. Independent variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…For instance, Kishi et al 2 ) reported that left hip rotation range of motion was lower in subjects with low back pain than in those without low back pain. With regard to muscle strength, Uritani et al 3 ) compared isometric strength measured at three different positions affected by hip flexion during hip internal rotation.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kishi et al 2 ) reported that left hip rotation range of motion was lower in subjects with low back pain than in those without low back pain. With regard to muscle strength, Uritani et al 3 ) compared isometric strength measured at three different positions affected by hip flexion during hip internal rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Kishi et al4 ) reported that left hip rotational ROM was lower in subjects with low back pain than in subjects without low back pain. Uritani et al 5. ) noted that isometric strength, measured at three different positions, was affected by hip flexion during hip internal rotation.…”
Section: Introductionmentioning
confidence: 99%